Level Kemampuan Penalaran Spasial Siswa SMA dengan Gaya Belajar Kinestetik dalam Menyelesaikan Masalah Geometri - Maftuh, Moh. Syukron; Ni’mah, Ashfa Wildatun (Universitas Nusantara PGRI Kediri, 2023)
This study aims to describe the level of spatial reasoning ability of high school students with a kinesthetic learning style in solving geometric problems. The subjects used in this study consisted of 2 students of class XII SMA Negeri 1 Kedamean Gresik. This research is a qualitative descriptive study. Data collection techniques in this research are spatial reasoning ability tests and interviews. Data analysis used in this study is data reduction, data presentation, and drawing conclusions. Researchers also used data analysis techniques from Milles & Huberman's research, namely data reduction, data presentation and drawing conclusions. Meanwhile, to check the validity of a data researcher uses source triangulation. The results showed that the subjects described the design model by looking at it as a real object, such as describing the problem as a robot composed of several cubes to form a robot and the image also resembles a water spray in the garden which is composed of several cubes and also the holes for the outlet. water. So that the subject is able to convert a two-dimensional icon into a three-dimensional one. The subject explained that the picture has 7 cubes, one of which is blocked by the previous cube and each cube has a hole. Whereas 1 large cube in the middle has 7 holes, so that the subject is able to make the correct relationship between two-dimensional icons and three-dimensional objects. The subject solves the problem by finding the volume of the cube first, that is, each cube has 27 unit cubes and is multiplied by the number of cubes and the result is subtracted by the number of holes in the cube. The subject is able to solve geometry problems correctly along with the steps and explanations. Thus the kinesthetic subject's spatial reasoning in solving geometric problems is included in the category of high-level spatial reasoning (spatial).